Fungsi Kesantunan Berbahasa dalam Interaksi Guru dan Murid di Lingkungan MIS Al Jihad Palangka Raya - Lilik Kholisotin; Lastaria Lastaria (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
Language politeness is a way of not giving a bad impression to the speaker or etiquette/ethics language. The formulation of the problem in this research are: (1) How is the function of linguistic politeness in teacher and student interaction in MIS Al Jihad Palangka Raya? This study aims to describe the function of language courtesy in the interaction of teachers and students in the environment of MIS Al Jihad Palangka Raya. The approach used in research is a pragmatic approach in which this approach is suitable for understanding language usage. The type of research used is qualitative. Meanwhile, the research method is descriptive aims to obtain information about the situation and see the relation between the variables that have been determined. Based on the results there are several functions of language politeness are: (1) Declarative function, there are explanatory sentences, declaring information, expressing congratulations, declaring a covenant, and declaring a warning; (2) Interrogative function, requesting an answer, asking for sincerity, asking permission, asking for reasons, asking for information, asking for opinions, and asking for sincerity; (3) imperative function, there enjoin, prohibit, ask for help, suggest, advocate, and express regret; (4) The apology function can be seen from the use of the word sorry and the form of interjection (speaker expression); and (5) Criticism, there is rejecting the answer, mentioning deficiencies, and calling error.